El estrés y su influencia en el desempeño académico de los estudiantes de la Carrera de Enfermería del primer semestre de la Universidad Técnica De Babahoyo. agosto 2018 – febrero 2019 - Fajardo Parra, Tania Jamileth (2019)
Introduction: Stress interferes with the educative process, normal and consequent that should be carried out in the student stage, likewise, as happens in daily life, will appear stressors series of which, it is sometimes difficult get off or get out. Objective: Identify how way stress influences on academic performance to students of nursing career of the first semester to Babahoyo´s Technical University. August 2018 – February 2019 Methodology: it is a mixed qualitative – quantitative approach, the non-experimental design, descriptive, field and transversal type. Using the inductive and historical – logical method. The population is constituted by 83 students of nursing career, with a sample of 81 obtained by non-probabilistic, of incidental or causal type in which many inclusion and exclusion criteria are appointed. There were used two instruments the Academic Stress Test (SISCO inventory) and the observation card for picking the general average. Results: the data was analyzed at Microsoft program as it is Excel, the inferential statistics test were Chi Cuadrado and correlacion de PEARSON, r=0.81. Where it was found that to 100% (79) students, the one the most incident at students was the medium stress 53% (42), and 58.23% (46), represented to goodly performance level. Conclusion: When performing the inferential analysis, statistically significant results were obtained r=0.81, which allowed accepted the investigation hypothesis.